Atomic photoionization: When does it actually begin? - Kheifets, A.; Ivanov, I.; Bray, Igor (2012)
We analyze a time delay of one- and two-electron photoemission from an atom after absorption of an attosecond XUV pulse. We establish this delay by solving the time dependent Schrödinger equation and by subsequent tracing of the field-free evolution of the photoelectron wave packet. This delay can also be related to the energy derivative of the phase of the complex photoionization amplitude which makes the time delay a sensitive probe of many-electron correlation.